Analisis Faktor-Faktor Yang Mempengaruhi Pemahaman Terhadap Standar Akuntansi Pemerintahan (SAP) Dalam Penyusunan Laporan Keuangan (Studi Kasus Pada Pemerintahan Provinsi Kepulauan Riau) - Rita Rita; Erman Sutandar (Institut Teknologi dan Bisnis Swadharma, 2020)
In terms of preparation of Regional Financial Reports, the Regional Government in addition to having an accounting policy as the basis for preparing financial reports, local governments must also have human resources capable of compiling regional financial reports in accordance with Government Regulation Number 24 of 2005 concerning Government Accounting Standards and Ministerial Regulations in Negeri Number 13 of 2006. This research will take the case of the factors that influence the understanding of SKPD and treasurer tools of Government Accounting Standards (SAP) in the preparation of regional financial statements. Based on the research data that has been collected, data on the demographics of research respondents are obtained, consisting of: (1) Educational Background, (2) Education Level, and (5) How many times have attended training on regional financial reporting. There is a positive relationship (correlation) between the dependent variable which shows that the variable has a unidirectional effect. Educational background, education level and training have a significant effect on the understanding of Government Accounting Standards in Regional Financial Reporting, and this is in line with the research hypothesis.